Quantitative analysis of fertilizer using laser-induced breakdown spectroscopy combined with random forest algorithm - Wei, Lai; Ding, Yu; Chen, Jing; Yang, Linyu; Wei, Jinyu; Shi, Yinan; Ma, Zigao; Wang, Zhiying; Chen, Wenjie; Zhao, Xingqiang (Frontiers in Chemistry, 2023)
Chemical fertilizers are important for effectively improving soil fertility, promoting crop growth, and increasing grain yield. Therefore, methods that can quickly and accurately measure the amount of fertilization in the soil should be developed. In this study, 20 groups of soil samples were analyzed using laser-induced breakdown spectroscopy, and partial least squares (PLS) and random forest (RF) models were established. The prediction performances of the models for the chemical fertilizer content and pH were analyzed as well. The experimental results showed that the R2 and root mean square error (RMSE) of the chemical fertilizer content in the soil obtained using the full-spectrum PLS model were 0.7852 and 2.2700 respectively. The predicted R2 for soil pH was 0.7290, and RMSE was 0.2364. At the same time, the full-spectrum RF model showed R2 of 0.9471 (an increase of 21%) and RMSE of 0.3021 (a decrease of 87%) for fertilizer content. R2 for the soil pH under the RF model was 0.9517 (an increase of 31%), whereas RMSE was 0.0298 (a decrease of 87%). Therefore, the RF model showed better prediction performance than the PLS model. The results of this study show that the combination of laser-induced breakdown spectroscopy with RF algorithm is a feasible method for rapid determination of soil fertilizer content.